Looking for answers? Westonci.ca is your go-to Q&A platform, offering quick, trustworthy responses from a community of experts. Get detailed and accurate answers to your questions from a dedicated community of experts on our Q&A platform. Join our platform to connect with experts ready to provide precise answers to your questions in different areas.
Sagot :
To factor the quadratic function [tex]\( f(x) = x^2 - 17x + 72 \)[/tex] and write it in intercept form, we follow these steps:
1. Identify the quadratic function:
The given function is [tex]\( f(x) = x^2 - 17x + 72 \)[/tex].
2. Identify the coefficients:
The quadratic function is in the form [tex]\( ax^2 + bx + c \)[/tex]. Here, [tex]\( a = 1 \)[/tex], [tex]\( b = -17 \)[/tex], and [tex]\( c = 72 \)[/tex].
3. Determine two numbers that multiply to [tex]\( c \)[/tex] and add to [tex]\( b \)[/tex]:
We need to find two numbers that multiply to 72 (the constant term [tex]\( c \)[/tex]) and add up to -17 (the coefficient of [tex]\( x \)[/tex]).
These two numbers are -9 and -8 because:
[tex]\[ (-9) \times (-8) = 72 \quad \text{(product)} \][/tex]
[tex]\[ (-9) + (-8) = -17 \quad \text{(sum)} \][/tex]
4. Rewrite the quadratic as a product of two binomials:
Using the numbers -9 and -8, we can factor the quadratic expression:
[tex]\[ f(x) = x^2 - 17x + 72 = (x - 9)(x - 8) \][/tex]
5. Final answer in intercept form:
The function [tex]\( f(x) \)[/tex] in intercept form is:
[tex]\[ f(x) = (x - 9)(x - 8) \][/tex]
So, the intercept form of the function is:
[tex]\[ f(x) = (x - 9)(x - 8) \][/tex]
1. Identify the quadratic function:
The given function is [tex]\( f(x) = x^2 - 17x + 72 \)[/tex].
2. Identify the coefficients:
The quadratic function is in the form [tex]\( ax^2 + bx + c \)[/tex]. Here, [tex]\( a = 1 \)[/tex], [tex]\( b = -17 \)[/tex], and [tex]\( c = 72 \)[/tex].
3. Determine two numbers that multiply to [tex]\( c \)[/tex] and add to [tex]\( b \)[/tex]:
We need to find two numbers that multiply to 72 (the constant term [tex]\( c \)[/tex]) and add up to -17 (the coefficient of [tex]\( x \)[/tex]).
These two numbers are -9 and -8 because:
[tex]\[ (-9) \times (-8) = 72 \quad \text{(product)} \][/tex]
[tex]\[ (-9) + (-8) = -17 \quad \text{(sum)} \][/tex]
4. Rewrite the quadratic as a product of two binomials:
Using the numbers -9 and -8, we can factor the quadratic expression:
[tex]\[ f(x) = x^2 - 17x + 72 = (x - 9)(x - 8) \][/tex]
5. Final answer in intercept form:
The function [tex]\( f(x) \)[/tex] in intercept form is:
[tex]\[ f(x) = (x - 9)(x - 8) \][/tex]
So, the intercept form of the function is:
[tex]\[ f(x) = (x - 9)(x - 8) \][/tex]
Thank you for your visit. We are dedicated to helping you find the information you need, whenever you need it. Thank you for your visit. We're committed to providing you with the best information available. Return anytime for more. Stay curious and keep coming back to Westonci.ca for answers to all your burning questions.